Making Aliens of Us: Self-Serving Vegetarianism in Percy Bysshe Shelley’s ‘A Vindication of Natural Diet’ and Desmond Stewart’s ‘The Limits of Trooghaft’ - Metcalfe, Ella (Leviathan: Interdisciplinary Journal in English, 2022)
In the first half of the nineteenth century, before Charles Darwin had made even a ripple in Western philosophy, one question seemed to be clattering its way through the minds of many: where is the human place in the natural world? If we were to imagine this role as a walking path laid down by nature long ago, then the humans (or human-representatives) in Percy Bysshe Shelley’s ‘A Vindication of Natural Diet’ and Desmond Stuart’s ‘The Limits of Trooghaft’ have long since strayed from the road. Shelley reveres vegetarianism as a return to a natural diet with the power to resolve this philosophical question, which is a self-indulgent form of vegetarianism that Stewart has no problem mimicking with mocking intent. Drawing upon the irony and anthropocentricism of his genres, Stewart presents an inwardly focused vegetarianism that only succeeds at leading humans as far from nature’s path as alien invaders.